2021
DOI: 10.1108/jarhe-07-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

The effect of students' conceptions of feedback on academic self-efficacy and self-regulation: evidence from higher education in Pakistan

Abstract: PurposeThis study investigated the influence of students' conceptions of feedback (ScoF) dimensions on academic self-efficacy (SE) and self-regulation (SRG).Design/methodology/approachThe study employed the partial least squares structural equation modeling (PLS-SEM) approach on a sample data of 528 students from ten different universities of Karachi city.FindingsResults indicate that active use of feedback (AUF) and enjoyment (ENJ) has a positive and significant impact on SE, while ignorance showed an adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
(80 reference statements)
2
15
0
Order By: Relevance
“…Findings of the study conclude that overall learning motivation through constructive feedback has a significant impact on students' academic achievement in Chemistry subject.This findings are aligned with Fatima et al (2021) who argued the same that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Findings of the study conclude that overall learning motivation through constructive feedback has a significant impact on students' academic achievement in Chemistry subject.This findings are aligned with Fatima et al (2021) who argued the same that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Findings of the qualitative data collected before and after the intervention from the teachers, headmistress, and students through interviews and focus group discussion reported that the constructive feedback intervention plays a significant role in increasing students' performance and motivation. Findings align with Fatima et al (2021), who argued the same point that feedback is an integral part of any performance test. Students take constructive feedback positively in the evaluation and perform better as they know that learning happens with practice (Selvaraj et al, 2021).…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…In contrast, high school students who have been exposed to student-centered assessment found value in using feedback (Harris et al, 2014). Correlational studies have provided support for the relationships that conceptions have with other motivational variables, including self-efficacy (Brown et al, 2016;Fatima et al, 2021) and goal orientation (Rakoczy et al, 2013), self-regulated learning (SRL) behaviors (Brown et al, 2016), satisfaction with feedback (Robinson et al, 2013), and academic performance (Brown et al, 2016).…”
Section: Conceptions Of Feedbackmentioning
confidence: 99%